2017
DOI: 10.1097/hjh.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

Ascending to descending aortic pulse pressure amplification in children

Abstract: The PP amplification is observed even in children. The degree of the PP amplification increases with age during childhood contrary to the relationship in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The negative correlation among PPA with TVR, AP, and reflection coefficient observed in the current study, reinforces the concept of the inverse association between PPA reduction and arterial stiffness. Different from Mukarami et al, in the present study, PPA did not correlated with age. It was also observed that AIx@75 was inversely related to the PPA in the DM1 group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The negative correlation among PPA with TVR, AP, and reflection coefficient observed in the current study, reinforces the concept of the inverse association between PPA reduction and arterial stiffness. Different from Mukarami et al, in the present study, PPA did not correlated with age. It was also observed that AIx@75 was inversely related to the PPA in the DM1 group.…”
Section: Discussioncontrasting
confidence: 99%
“…The PPp/PPc ratio, also known as pulse pressure amplification (PPA), is an important physiological function to protect the heart against afterload and microcirculation from pulsatile pressure stress. Mukarami et al demonstrated that PPA is present in children. Contrary to what happens with adult population, PPA increases in with age during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed that contrary to what happens in adulthood, PPA increases during childhood. Mukarami et al evaluated PPA in two ways: by the difference between PP in the descending aorta and PP in the ascending aorta, and by the PP descending / PP ascending ratio [ 11 ]. These same authors also showed a reduction in PPA in patients after aortic arch repair when compared to the control group [ 12 ] and after surgery for complete transposition of great arteries [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mukarami et al were the first to study PPA in children and adolescents. These authors observed that PPA is present in children, but contrary to what happens in adulthood, it increases during childhood [ 11 ]. These same authors also showed a reduction in PPA in patients after aortic arch repair when compared to the control group [ 12 ] and after surgery for complete transposition of great arteries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Identifying the components of early life blood pressure(BP) are of critical importance as evidence builds on the role of BP in predicting future atherosclerotic cardiovascular disease (ASCVD). Classic literature has demonstrated the ability for historical BP to predict presence of atherosclerotic plaque in younger persons victim to unfortunate mortality like accident and war.…”
mentioning
confidence: 99%